2018
DOI: 10.1016/j.ihj.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

One-year clinical outcomes of different coronary drug eluting stents—Data from a prospective registry

Abstract: We compared one-year clinical outcomes of different drug eluting stents (DES) used in a prospective observation registry maintained in two hospitals over three years. The primary endpoint was combination of all-cause mortality, stent thrombosis and revascularization. There was no significant difference among different DES. We grouped DES into well-evaluated Imported DES (Imported group), which used to be expensive prior to price control and economical Indian DES (Indigenous group) that lack supportive clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Some studies have suggested that, compared to first-generation DES, second-generation DES are associated with better vascular healing, lower prevalence of neoatherosclerosis and reduction in the incidence of unstable features such as disrupted neointima, thin-cap fibroatheroma, thrombus and fibrin deposition [27, 28]. In our setting, a plethora of stent types with various combinations of anti-proliferative drugs and polymers are available which makes it difficult to analyse the results stratified by stent types [29]. Mechanisms underlying ACS presentations with various stent types need further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that, compared to first-generation DES, second-generation DES are associated with better vascular healing, lower prevalence of neoatherosclerosis and reduction in the incidence of unstable features such as disrupted neointima, thin-cap fibroatheroma, thrombus and fibrin deposition [27, 28]. In our setting, a plethora of stent types with various combinations of anti-proliferative drugs and polymers are available which makes it difficult to analyse the results stratified by stent types [29]. Mechanisms underlying ACS presentations with various stent types need further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the impact of the type of DES on clinical presentation could not be compared. However, in developing countries like ours, a variety of stent types with various combinations of anti-proliferative drugs and polymers are available which makes it difficult to segregate them into two or three groups for study purposes [29].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although restenosis still develops after modern DES in 5 to 10% patients, 3,4 and this has become a common clinical problem despite widespread use of 3rd generation DES. 5,6 however, if we compare it with BMS stent restenosis, DES restenosis treatment is associated with poor long-term outcomes; present data suggest that after repeat stenting, 10-20% of these patients go on to develop recurrent restenosis. 7,8 Coronary intervention with stenting is best treatment modality for both acute coronary syndrome and stable ischemic heart disease.…”
Section: Introductionmentioning
confidence: 80%
“…Although there is no scientific difference between indigenously developed DES vs those developed and marketed by global manufacturers, cost effectiveness remains a key factor in the decision-making process for patients and health care providers in India[21]. The most promising results of this retrospective study are 100% procedural success rate and low rates of MACE (4.87%).…”
Section: Discussionmentioning
confidence: 96%